The Impact of Face-to-Face Pharmacist Transitional Care Management Visits on Medication-Related Problems. (June 2020) - Mayzel, Bianca; Axtell, Sandra; Richardson, Carolyn; Link, Nicholas
Background: Studies are needed to evaluate medication-related problems (MRPs) to assess the effect of a pharmacist on managing medications postdischarge.Objective: To assess the ability of pharmacist-led medication review and reconciliation to reduce the number of MRPs found in transitional care medicine (TCM) visits, leading to medication optimization.Methods: This study involved a retrospective chart review of standard TCM procedure at a family/internal medicine clinic and a prospective, team-based TCM visit in the same clinic. Inclusion criteria included patients discharged from any hospital within our institution and seen in the clinic. The primary outcome was the difference in the proportion of MRPs found between the prospective and retrospective groups. Secondary outcomes included the number and specific type of MRPs found, classified by the Pharmaceutical Care Network Europe tool, and further subdivided by patient aware or unaware of MRP, only in the prospective group, as well as 30-day readmission rate.Results: Patients in the prospective group (n = 50) had an average age of 67.9 years versus 65.5 years in the retrospective group (n = 50). Four times as many patients in the prospective group were found to have MRPs than the retrospective group. The most common MRP was due to a patient-related factor, meaning the cause is related to a patient's behavior. Patients were unaware of the MRP in a majority of these cases. Thirty-day readmission rate did not differ between the groups.Conclusion: Team-based TCM visits that included a pharmacist-led medication reconciliation uncovered more MRPs than patients who did not have a pharmacist perform a medication reconciliation.